Papers from the XIIth Linguistic Symposium on Romance Languages - Baldi, Philip (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 1984)
This volume contains a selection of papers presented at the XII Linguistic Symposium on Romance Languages (LSRL), held in April 1982 at Penn State University. These papers reflect the general state of the art in Romance Linguistics. Some of the studies are theoretical papers that seek to establish general principles based on the analysis of a Romance language, others apply the principles of a particular theory to the solution of a problem in some Romance language, or provide data-oriented descriptions of linguistic phenomena in Romance languages.